The ghosts in the archive: World War Two photography and landscapes crafted by the Nazis in Finland. (1st October 2020) - Matila, Tuuli
ABSTRACT: The Finnish wartime landscape was altered by Nazi troops who were stationed there during World War Two. This paper examines wartime sceneries through Finnish Army Information Company's photographs from the period of the war known in Finland as the Continuation War (1941–1944). The images reveal a completely different side to the Nazi co-belligerence to what is traditionally acknowledged in Finland. I discuss the ways the Nazi troops altered the Finnish landscape, adding `German-ness´ to their surroundings and more specifically, how Nazi ideology manifested in the northern Finnish landscapes. The Finns have been completely oblivious to the symbolic messages the Nazis crafted in their surroundings. Photographs as haunting representation addresses in this paper both the difficult memory of German presence that frames these pictures and the specific potency of these photographic encounters. Haunting as a theory deals with the evocative ways an image can convey information about the past.